Antiplatelet drug selection in PCI to vein grafts in patients with acute coronary syndrome and adverse clinical outcomes: Insights from the British Cardiovascular Intervention Society database. Issue 4 (22nd January 2018) - Sirker, Alex; Kwok, Chun Shing; Kontopantelis, Evangelos; Johnson, Tom; Freeman, Philip; de Belder, Mark A; Ludman, Peter; Zaman, Azfar; Mamas, Mamas A
Abstract: Objective: This study aims to evaluate outcomes associated with different P2Y12 agents in Saphenous Vein graft (SVG) percutaneous coronary intervention (PCI). Background: SVG PCI is associated with greater risks of ischemic complications, compared with native coronary PCI. Outcomes associated with the use of potent P2Y12 blocking drugs, Prasugrel and Ticagrelor, in SVG PCI are unknown. Methods: Patients included in the study underwent SVG PCI in the United Kingdom between 2007 and 2014 for acute coronary syndrome and were grouped by P2Y12 antiplatelet use. In‐hospital major adverse cardiac events, major bleeding and 30‐day and 1‐year mortality were examined. Multiple imputations with chained equations to impute missing data were used. Adjustment for baseline imbalances was performed using (1) multiple logistic regression (MLR) and (separately) (2) propensity score matching (PSM). Results: Data weres analyzed from 8, 119 patients and most cases were treated with Clopidogrel ( n  = 7, 401), followed by Ticagrelor ( n  = 497) and Prasugrel ( n  = 221). In both MLR and PSM models, there was no significant evidence to suggest that either Prasugrel or Ticagrelor was associated with significantly lower 30‐day mortality compared with Clopidogrel. The odds ratios reported from the multivariable analysis were 1.22 (95% CI: 0.60–2.51) for Prasugrel vs. Clopidogrel and 0.48 (95% CI: 0.20–1.16) for Ticagrelor vs. Clopidogrel. No significant differences were seen for in‐hospital ischemic or bleeding events. Conclusions: Our real world national study provides no clear evidence to indicate that use of potent P2Y12 blockers in SVG PCI is associated with improved clinical outcomes.